2007
DOI: 10.1002/chem.200601727
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Synthesis of Lanthanide Phosphate Nanocrystals

Abstract: Uniform LnPO(4).x H(2)O (Ln=Y, La-Nd, Sm-Lu) nanocrystals that have controllable 0D (spherelike), 1D (rodlike), and 2D (polygonlike) structures have been systematically synthesized by means of a hydrothermal method by using a mixed solvent of water and ethanol. Transmission electron microscopy images and SEAD (selected area electron diffraction) patterns revealed that the products are highly crystalline and have structurally uniform shapes. IR, Raman, and electron energy loss spectroscopies gave spectra that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 39 publications
1
81
0
Order By: Relevance
“…[15] Thus, two key factors controlling the properties of nanomaterials are the size and surface characteristics of the nanoparticles. [16][17][18][19] Admittedly, the contention that the size of nanocrystals determines their surface area has been fundamentally accepted; these two factors are interrelated. The nucleation and growth processes of these nanocrystals have been carefully discussed and explained by the Peng group regarding the preparation of semiconductors.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[15] Thus, two key factors controlling the properties of nanomaterials are the size and surface characteristics of the nanoparticles. [16][17][18][19] Admittedly, the contention that the size of nanocrystals determines their surface area has been fundamentally accepted; these two factors are interrelated. The nucleation and growth processes of these nanocrystals have been carefully discussed and explained by the Peng group regarding the preparation of semiconductors.…”
Section: Introductionmentioning
confidence: 98%
“…[20][21][22] Research on how to prepare nanocrystals with controllable sizes and shapes have been reported universally. [12,18,19,[21][22][23][24][25][26][27][28][29][30][31] However, one of the major challenges in the synthesis of nanomaterials is still to gain a comprehensive understanding of monodisperse nanocrystal nucleation and growth, and furthermore, a general and convenient approach to adjust the SSA and control the total surface area of the nanocrystal units, that is, the average surface/atom ratio (d) of inorganic nanomaterials. To meet this challenge, the emphasis of this work is based on a mechanism of surface chemical thermodynamics that can explain the relation between the initial concentration of reactants and the average d value of the final products by a unified and relatively simple synthetic condition alteration.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure yields rounded NPs of NaYF 4 ( Figure 1G) 4 , NaOH and oleic acid in a water/ ethanol solution at temperatures ranging from 100 to 140°C [116]. Likewise, REPO 4 · H 2 O (RE = Y, La-Nd, Sm-Lu) of different morphologies (sphere-like, rod-like and polygon-like, with sizes ranging from 8 to 60 nm, depending on the RE) were synthesized from RE nitrate, NaH 2 PO 4 , oleic acid, and NaOH solutions in water and ethanol treated at 140°C [117]. However, the use of hydrophobic additives finally produces hydrophobic NPs, thus demanding further functionalization treatments.…”
Section: Hydro(solvo)thermal Methodsmentioning
confidence: 99%
“…The crystal structures of LnPO 4 NPs exhibit multiple polymorphic forms with non-centrosymmetric and centrosymmetric symmetry. [ 28 ] Therefore, the centrosymmetric LaPO 4 and non-centrosymmetric hydrated TbPO 4 were selected for the synthesis of homogeneous nanoscale La-Tb phosphate solid solution (La 1−x Tb x PO 4 ). The nanomaterials can be modulated from centrosymmetric to non-centrosymmetric by continuously changing the Tb 3 + content from 0 to 100 mol%.…”
Section: Doi: 101002/adma201104297mentioning
confidence: 99%